Political Transition and Democratic Teachers: Negotiating Citizenship in the Spanish Education System. (April 2014) - Groves, Tamar
The success of Spain's transformation from a dictatorship to a stable democracy has triggered a lively discussion about the factors which contributed to the process. The question of civic participation in Spain's political transformation has proved highly controversial and I suggest that observing professional domains and their implications for citizen formation processes provides a new way to evaluate the civic contribution to Spain's democratization. Spanish teachers mobilized in the 1970s around two main issues: their working conditions and pedagogical methods. This article focuses on the implications of their common struggle to articulate, construct and disseminate democratic citizenship. It shows how they contributed to free deliberation, civic involvement and citizen empowerment, aspiring to supplement the concept of citizenship with those of active participation in community organizations, knowledge of governmental procedures, critical assessment of social, political and economic structures and addressing areas of injustice.